Study of Root Exudate Organic Acids and Microbial Population in the Rhizosphere of Oil Palm Seedling - Anandyawati, .; Sumarsih, Enok; Nugroho, Budi; Widyastuti, Rahayu (UNIVERSITY OF LAMPUNG, 2017)
Mutual interaction between plants and microbes occured in the rhizosphere is expected to increase productivity of crops or soil fertility for agriculture. Plants excrete root exudates to attract microbes, and then microbes obtain habitat and food supply from plants and can fulfill the nutrient requirements through assisted enzymatic activity. The objective of the research was to study the types and amounts of root exudate organic acids, microbial population, and the relationship between root exudate organic acids and microbial population in the rhizosphere of oil palm seedlings. The study was conducted in a greenhouse using a planting medium of sterile quartz sand. The study was conducted using two factorials completely randomized design with three replications. The first factor was oil palm seedling age (control / no oil palm seed, 1, 3, 6, 9 and 12 months-old of oil palm seedlings) and the second factor was the periods of seedling growth (45, 90, 135 and 180 days), so in total there were 72 experimental units. The result of High Pressure Liquid Chromatography (HPLC) analysis revealed that four kinds of organic acids were observed in the rhizosphere of oil palm seedlings, with the highest concentration were: acetic acid (1.66 ppm), citric acid (0.157 ppm), malic acid (2.061 ppm) and oxalic acid (0.675) ppm. The highest total population of microbes, fungi, Azotobacter, phosphate solubilizing bacteria (PSB) and phosphate solubilizing fungi (PSF) were 19.38 × 106 cfu g-1 soil, 3.28 × 104 cfu g-1 soil, 12.09 × 105 cfu g-1 soil, 8.39 × 104 cfu g-1 soil and 1.15 × 104 cfu g-1 soil, respectively. There are positive correlations between root exudate organic acids and total microbes, fungi, Azotobacter, PSB and PSF are.Keywords: microbes, organic acids, rhizosphere, root exudates